PLAIO Introduction from the Editors (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Since 2012, when PLAIO was first published, the journal has sought to provide a space in which ideas, practices, policies, and research around the evaluation of so-called “prior learning” could be brought together and shared. In many ways, we have seen PLAIO as part of a broad international movement for social change and social justice that questions taken-for-granted understandings about learning, expertise, and assessment. Taken as a whole, the PLA/RPL/VPL agenda offers a critical perspective and alternatives to conventional assumptions about how we define and evaluate knowledge, what we assume about those who know, and how those bypassed by academic and work-related institutions can be properly recognized.The 12 published issues of PLAIO have highlighted the remarkable growth of the “validation of prior learning” movement and its worldwide scope. This movement has influenced local, regional, national, and international policy bodies; reshaped how we think about the fairness of evaluation standards; and encouraged critical reflection on the tools used to judge skills, knowledge, and competencies. It has reminded educators, policymakers, and practitioners that “access” as an ideal requires ongoing scrutiny of who is included, how they are treated, and how learning acquired at home, in communities, and in the workplace is granted legitimacy.At the same time, we recognize that the PLA/RPL/VPL terrain is complex, multilayered, and shaped by value judgments. The language of assessment, the rubrics we construct, and the credentialing models we rely on all reflect—sometimes explicitly, sometimes tacitly—assumptions about who knows and how knowledge is validated. Even as we acknowledge many successes, the central question remains: who is still excluded, and whose ways of knowing fall outside established standards? As the issues and challenges reflected in PLAIO demonstrate, much work remains to be done.The 23rd International Conference on Open Education and Recognition Technologies, Practices and Policies (ePIC), held in Paris in October 2025, provided an important opportunity to deepen these questions. The conference theme, “From Open Education to Open Recognition,” invited reflection on what we mean by “open” and why “recognition” must be central to this agenda.Open recognition assumes that learning can be recognized beyond the boundaries of university or governmental structures and calls for a reconfiguration of how legitimacy in knowledge is constructed. It foregrounds practices such as open badges for workplace-acquired skills, which offer credible evidence of knowledge and ability without relying solely on traditional institutional credentials. In doing so, open recognition challenges established hierarchies of knowledge validation and creates new pathways for learners whose competencies are developed in diverse, often informal, or work-based contexts.“The Paris Declaration on the Equality of Recognitions,” the provocative centerpiece of ePIC 2025, reinforces this shift by affirming that “recognition is a fundamental human practice.” Read through the lens of open recognition, this principle gains further depth: it not only positions recognition as a right but also calls for plural, distributed, and accessible systems of validation that extend beyond institutional gatekeeping. This resonates strongly with PLAIO’s ongoing efforts and its broader emancipatory ambition—one that seeks not only to question existing systems of recognition but also to reshape them to include diverse forms of knowing and competence.We are therefore pleased to present this special issue of PLAIO in two parts: Part I (this current publication) contains abstracts of the ePIC sessions and panels, edited by authors and editors; Part II (forthcoming) will include edited texts and related materials provided by presenters. In this spirit of openness and shared recognition, we are grateful to Serge Ravet, Don Presant, and Deb Carr, members of the ePIC 2025 Organizing Committee, who joined us in editing this issue and contributed a more detailed introduction. Their longstanding engagement with open recognition further strengthens this issue’s contribution to rethinking how learning is valued across contexts. We also thank all who gathered in Paris for this inspiring and idea-rich international exchange.A note on our process: All presenters at ePIC 2025 were invited to edit session abstracts that were included in the conference program. When we did not receive a response, we lightly edited each document that is contained in PLAIO. Occasionally, the editors used AI to help extract information about a session from the transcript of a recording to help clarify what the presenters spoke about in their session. We are thus very pleased that all ePIC 2025 sessions are accounted for in Part I of this PLAIO Special Issue. Great thanks to our SUNY Empire State University colleagues, Alexa Collesides and Amy Giaculli for their invaluable help in preparing this issue of PLAIO.